High-density effects due to interaction of self-trapped exciton with (Ba, 5p) core hole in BaF2 at low temperature - Terekhin, M.A.; Svechnikov, N.Yu.; Tanaka, S.; Hirose, S.; Kamada, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The effect of VUV undulator excitation intensity on the emission shape and decay time of BaF2 crystal at low temperature has been observed. The findings are explained in terms of quenching of Auger-free luminescence (cross luminescence) by self-trapped exciton via Forster mechanism energy transfer.